Availability of Zika Virus Information on County and Regional Health Department Websites in the State of Texas [20O]. (May 2017) - Sullivan, Adriana; Page-Ramsey, Sarah M.; Ireland, Kayla; Cuvillier, James; Ramsey, Patrick S.; Rodriguez, Emma
Abstract : INTRODUCTION: Zika virus infection is an emerging health threat in pregnant women, particularly in Texas. It is important that obstetric patients and providers can access up-to-date information about Zika. Our objective was to evaluate the availability of information about the Zika virus and perinatal risks on local health department websites in Texas. METHODS: We reviewed all Texas county, regional, and metropolitan health department websites for general information available on the Zika virus, pregnancy related risks, prevention measures, mosquito repellent use, sexual transmission, endemic areas, travel guidance, and pregnancy planning. In cases where information was not available on the main webpage, an internal search of the site using the term "Zika" was performed. RESULTS: General information about Zika virus was found on only 13.8% of 254 county public health websites, 18.1% of 11 public health region websites, and 51.3% of 39 metropolitan websites. Available county information included patient education (54.3% of sites), health care provider materials (31.4%), details about Zika virus (62.9%), pregnancy risks (37.1%), sexual transmission (40.0%), use of mosquito repellents (34.3%), travel avoidance (42.9%), pregnancy timing (22.9%), and Zika endemic countries (40.0%). Similar rates of information available in these categories were observed on the regional and metropolitan websites. CONCLUSION: Despite growing concerns about perinatal risks and Zika virus, local health department websites in Texas have limited information for patients and providers. While state and national level information about perinatal risks from Zika virus is available, enhanced local efforts are needed to improve education and preparedness of patients and providers.